Capnography During Procedural Sedation and Analgesia with Intramuscular Ketamine in Paediatric Patients - Seyedhossein Seyedhosseini-davarani; Hamideh Akbari; Sepideh Babaniamansour; Ehsan Aliniagerdroudbari; Ehsan Karimialavijeh (Galenos Yayinevi, 2021)
Introduction:Capnography is a proven effective tool for procedural sedation and analgesia (PSA); however it is hardly available in developing countries like Iran. This study aimed to discover the frequency of hypoventilation in paediatric patients who received intramuscular (IM) ketamine and evaluate the relationship between end-tidal carbon dioxide (ETCO2) changes and other vital signs.Methods:This was a cross-sectional study conducted in 2019. Paediatric patients (under 14 years old) who underwent PSA with 5 mg/kg of ketamine given IM participated in this study. ETCO2 was monitored by the mainstream CO2 sensor. Hypoventilation was defined as ETCO2 variation >10 mmHg from the baseline. Patients ETCO2, oxygen saturation (SPO2), pulse rate (PR), respiratory rate (RR) and blood pressure (BP) were continuously monitored and recorded. The specificity and sensitivity of SPO2 for detecting 10 mmHg change in the ETCO2 level were calculated. In addition, the PR, RR and BP were grouped based on patients' age (1-3 and 3-6 years) and compared between patients who had hypoventilation and others.Results:A total of 121 patients were enrolled in the study. The mean ± standard deviation of age was 2.89±1.48 years (minimum =1.2 and maximum =5.8 years). Nineteen (15.7%) patients had >10 mmHg changes in the ETCO2 level. In both age groups, PR and RR had a significant difference between patients with hypoventilation and other patients (p=0.001 in 1-3 years and 0.003 in 3-6 years).Conclusion:Hypoventilation was frequent among paediatric patients who received IM ketamine; however, it was minimal and required simple airway manoeuvres. Pulse oximetry was not accurate to detect this small amount of hypoventilation. Thus, capnography would provide better monitoring during ketamine PSA.